Effect of vitamin A supplementation in women of reproductive age on cause-specific early and late infant mortality in rural Ghana: ObaapaVitA double-blind, cluster-randomised, placebo-controlled trial. Issue 1 (4th January 2012) - Edmond, Karen; Hurt, Lisa; Fenty, Justin; Amenga-Etego, Seeba; Zandoh, Charles; Hurt, Chris; Danso, Samuel; Tawiah, Charlotte; Hill, Zelee; ten Asbroek, Augustinus H A; Owusu-Agyei, Seth; Campbell, Oona; et al.
Abstract : Objectives: To assess the effect of vitamin A supplementation in women of reproductive age in Ghana on cause- and age-specific infant mortality. In addition, because of recently published studies from Guinea Bissau, effects on infant mortality by sex and season were assessed. Design: Double-blind, cluster-randomised, placebo-controlled trial. Setting: 7 contiguous districts in the Brong Ahafo region of Ghana. Participants: All women of reproductive age (15–45 years) resident in the study area randomised by cluster of residence. All live born infants from 1 June 2003 to 30 September 2008 followed up through 4-weekly home visits. Intervention: Weekly low-dose (25 000 IU) vitamin A. Main outcome measures: Early infant mortality (1–5 months); late infant mortality (6–11 months); infection-specific infant mortality (0–11 months). Results: 1086 clusters, 62 662 live births, 52 574 infant-years and 3268 deaths yielded HRs (95% CIs) comparing weekly vitamin A with placebo: 1.04 (0.88 to 1.05) early infant mortality; 0.99 (0.84 to 1.18) late infant mortality; 1.03 (0.92 to 1.16) infection-specific infant mortality. There was no evidence of modification of the effect of vitamin A supplementation on infant mortality by sex (Wald statistic =0.07, p=0.80) or season (Wald statistic =0.03, p=0.86). Conclusions: This is the largest analysis of cause of infant deaths from Africa to date. Weekly vitamin A supplementation in women of reproductive age has no beneficial or deleterious effect on the causes of infant death to age 6 or 12 months in rural Ghana. Trial registration number: http://ClinicalTrials.gov : NCT00211341 .